Análise isotópica do carbono em néctares de caju - Figueira, Ricardo [UNESP]; Nogueira, Andressa Milene Parente [UNESP]; Ducatti, Carlos [UNESP]; Mischan, Martha Maria [UNESP]; Venturini Filho, Waldemar Gastoni [UNESP] (My University, 2011)
The objective of this work were to determine the isotopic composition of commercial cashew nectar and by mixture models, to quantify the carbon from plants holding the C3 photosynthetic cycle so as to identify beverages that don’t abide with the rules from the Brazilian legislation. The nectars were produced in a laboratory according to Brazilian law. Adulterated nectar was also produced with a quantity of cashew pulp below the allowed limit. In these beverages were calculated the theoretical percentages of C3 source, by using the mass balance of soluble solids. For the isotope analysis the isotope values of cane sugar, cashew nectars and its fractions purifi ed sugar and insoluble solids were measured. With these values were calculated the practical percentage of C3 (real) source through the isotopic analysis in a mass spectrometer. The practical results were compared with the theoretical ones to defi ne the best way to quantify the C3 source. To identify the adulterated commercial nectars was measured to the legality limit according to the Brazilian legislation. Four trademarks of cashew nectars were analyzed and all of them classifi ed legal. The legal limit enabled to identify the beverages in accordance with Brazilian law. The methodology was effi cient for measuring the carbon from C3 source in commercial cashew nectar.

Os objetivos deste trabalho foram determinar a composição isotópica de néctares comerciais de caju e, por meio de modelos de mistura, quantifi car aporcentagem de carbono proveniente de plantas do ciclo fotossintético C3 , a fi m de identifi car as bebidas que não estavam em conformidade com as normas do Ministério da Agricultura, Pecuária e Abastecimento (MAPA). Para isso, foram produzidos néctares em laboratório conforme a legislação brasileira. Também foi produzida bebida adulterada com quantidade de polpa de caju abaixo do limite estabelecido. Nesses néctares, as porcentagens teóricas de fonte C3 foram calculadas por meio do balanço de massa de sólidos solú- veis. Para a análise isotópica foram mensurados os valores isotópicos dos açúcares de cana, dos néctares de caju e de suas frações açúcares purifi cados e sólidos insolúveis. Com esses valores, foram calculadas as porcentagens práticas de fonte C3 (reais) por meio da análise isotópica, em espectrô- metro de massa. Os resultados práticos foram comparados com os teóricos para defi nir a melhor forma de quantifi - cação de fonte C3 . Para identifi car os néctares comerciais adulterados, foi desenvolvido um limite de legalidade conforme a legislação brasileira. Quatro marcas de néctares de caju foram analisadas e todas classifi cadas como legais. O limite de legalidade possibilitou identifi car as bebidas em conformidade com a lei. A metodologia foi efi ciente para quantifi car o carbono de origem C3 em néctares comerciais de caju.
Carbon isotope analysis in cashew nectars
Keywords: Beverages; Adulteration; Quality; Carbon-13; IRMS; Anacardium occidentale; Bebidas; Adulteração; Qualidade; Carbono-13; IRMS; Anacardium occidentale